Kyle finds her way - Salom, Susie (New York : Scholastic, 2016)
On her first day in sixth grade Kyle Constantini punches a bully who is bothering Marcy, a deaf classmate--and so begins her tumultuous year at Georgia O'Keeffe Middle School, in a different school than her twin brother, with new friends, new enemies, and the regional NAVS competition to come.
M
750
M
Keywords: Middle schools -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Friendship -- Juvenile fiction; Deaf children -- Juvenile fiction; Bullies -- Juvenile fiction; Orienteering -- Juvenile fiction; Middle schools -- Fiction; Schools -- Fiction; Twins -- Fiction; Siblings -- Fiction; Friendship -- Fiction; Deaf -- Fiction; People with disabilities -- Fiction; Bullies and bullying -- Fiction; Orienteering -- Fiction